Pengaruh efikasi diri dan dukungan sosial teman sebaya terhadap prestasi belajar - Syahrudin Syahrudin (Fakultas Psikologi, 2019)
Learning achievement is influenced by several factors such as internal factors or external factors. The purpose of this study is to determine the effect of self-efficacy and social support of peers on learning achievement simultaneously or together. The sampling technique uses simple random sampling in one of the existing SMA N in Woha District, Bima Regency, West Nusa Tenggara. The subjects in this study were 150 high school students in class X. The method of data collection in this study uses a scale of self-efficacy and social support of peers and reporr cards. The results of the multiple regression test analysis showed that self-efficacy and social support of peers simultaneously or simultaneously affect the learning achievement with an influence contribution of 25,0%.